2019
DOI: 10.1080/08927014.2019.1602123
|View full text |Cite
|
Sign up to set email alerts
|

The complex barnacle perfume: identification of waterborne pheromone homologues inBalanus improvisusand their differential expression during settlement

Abstract: A key question in barnacle biology is the nature of cues that induce gregarious settlement. One of the characterised cues is the waterborne settlement pheromone (WSP). This study aimed to identify WSP homologues in Balanus improvisus and to investigate their expression during settlement. Six WSP homologues were identified, all containing an N-terminal signal peptide, a conserved core region, and a variable C-terminus comprising several-GRand -HDDH-motifs. The B. improvisus WSP homologues were expressed in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…We here provide an initial genome characterization of the biotechnologically important bay barnacle B. improvisus , regarding genome size, repeat content, nucleotide diversity, and gene structure. Despite the fact that our pilot genome assembly is highly fragmented, such an assembly can be very useful in order to investigate specific genes and gene families (Lind et al 2010 , 2013 , 2017 ; Abramova et al 2019 ). It is also an important resource in designing future genome projects aiming for a high-quality reference genome.…”
Section: Discussionmentioning
confidence: 99%
“…We here provide an initial genome characterization of the biotechnologically important bay barnacle B. improvisus , regarding genome size, repeat content, nucleotide diversity, and gene structure. Despite the fact that our pilot genome assembly is highly fragmented, such an assembly can be very useful in order to investigate specific genes and gene families (Lind et al 2010 , 2013 , 2017 ; Abramova et al 2019 ). It is also an important resource in designing future genome projects aiming for a high-quality reference genome.…”
Section: Discussionmentioning
confidence: 99%
“…A major driver of larval settlement is conspecific chemical cues indicating the presence of other barnacles [70,71] while on the other hand they may be repelled by the presence of predatory organisms [26]. During this process, the larvae hover across the substrata and secrete temporary adhesives to guide other incoming larvae to settle nearby resulting in a higher number of cues left by the larvae on attractive substrata [71]. Larvae seem to have a selective preference for hydrophilic substrata and with initially high critical surface energy [18].…”
Section: Life Cyclementioning
confidence: 99%
“…All peptide sequences determined by amino acid sequencing were contained in the structure of WSP. Our sequence has already been cited in a recent study (Abramova et al, 2019) that showed discussed gene structure of WSP and its homologs in A. amphitrite and A. improvisus. Recombinant WSP showed a single band in SDS-PAGE with a relative molecular mass of 28.1 kDa (Figure S1).…”
Section: Results Cdna Cloning and Recombinant Proteinmentioning
confidence: 83%
“…In 2012, we sequenced more peptide fragments and determined the full-length cDNA sequence deposited in EMBL/Genbank/DDBJ databases as unpublished data (accession number AB695090), which is reported in this paper. Among the WSP homologs in A. amphitrite, this one is highly expressed during settlement (Abramova et al, 2019) and most concentrated in the cement of adult barnacles (So et al, 2017;Schultzhaus et al, 2019;Schultzhaus et al, 2020), supporting the idea that the "original WSP" is a major cyprid attractant among WSP homologs. In the present study, we extended our studies on the "original WSP" (hereafter, "WSP").…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation